Blood–Brain Barrier Compromise Does Not Predict Perihematoma Edema Growth in Intracerebral Hemorrhage. Issue 4 (April 2015) - McCourt, Rebecca; Gould, Bronwen; Kate, Mahesh; Asdaghi, Negar; Kosior, Jayme C.; Coutts, Shelagh; Hill, Michael D.; Demchuk, Andrew; Jeerakathil, Thomas; Emery, Derek; Butcher, Kenneth S.
<x xml:space="preserve">Abstract</x> Background and Purpose— There are limited data on the extent of blood–brain barrier (BBB) compromise in acute intracerebral hemorrhage patients. We tested the hypotheses that BBB compromise measured with permeability-surface area product (PS) is increased in the perihematoma region and predicts perihematoma edema growth in acute intracerebral hemorrhage patients. Methods— Patients were randomized within 24 hours of symptom onset to a systolic blood pressure (SBP) treatment of <150 (n=26) or <180 mm Hg (n=27). Permeability maps were generated using computed tomographic perfusion source data acquired 2 hours after randomization, and mean PS was measured in the hematoma, perihematoma, and hemispheric regions. Hematoma and edema volumes were measured on noncontrast computed tomographic scans obtained at baseline, 2 hours and 24 hours after randomization. Results— Patients were randomized at a median (interquartile range) time of 9.3 hours (14.1) from symptom onset. Treatment groups were balanced with respect to baseline SBP and hematoma volume. Perihematoma PS (5.1±2.4 mL/100 mL per minute) was higher than PS in contralateral regions (3.6±1.7 mL/100 mL per minute; P<0.001). Relative edema growth (0–24 hours) was not predicted by perihematoma PS (β=−0.192 [−0.06 to 0.01]) or SBP change (β=−0.092 [−0.002 to 0.001]). SBP was lower in the <150 target group (139.2±22.1 mm Hg) than in the <180 group (159.7±12.3 mm Hg; P<0.0001). Perihematoma PS was not different between groups (4.9±2.4 mL/100 mL per minute for the <150 group, 5.3±2.4 mL/100 mL per minute for the <180 group; P=0.51). Conclusions— BBB permeability is focally increased in the hematoma and perihematoma regions of acute intracerebral hemorrhage patients. BBB compromise does not predict acute perihematoma edema volume or edema growth. SBP reduction does not affect BBB permeability. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00963976.